P13 Safety of pirfenidone in patients with idiopathic pulmonary fibrosis (IPF): Integrated analysis of cumulative data from 5 clinical trials. (12th November 2015) - Noble, PW; Albera, C; Bradford, WZ; Costabel, U; Glaspole, I; Glassberg, MK; Lederer, DJ; Lin, Z; Nathan, SD; Pereira, CA; Swigris, JJ; Valeyre, D; et al.
Abstract : Introduction and objectives: IPF is a chronic, progressive and irreversible disease that requires long-term clinical management. To further evaluate the clinical safety of pirfenidone in patients with IPF, we performed a comprehensive integrated analysis of safety data from 5 clinical trials. Methods: All patients assigned to receive pirfenidone (2403 mg/d) in the Phase 3 ASCEND (016) and CAPACITY (004/006) studies and all patients receiving ≥1 dose of pirfenidone in either of two ongoing open-label studies (studies 002 and 012) comprised the integrated population. EAP (002) is a compassionate use study in the U.S.; RECAP (012) is evaluating pirfenidone in patients who completed one of the Phase 3 studies. Analyses were based on the January 15, 2014 interim data cut. Results: 1299 patients were included in the integrated population. The cumulative total exposure to pirfenidone was 3160 person exposure years (PEY). The median duration of exposure was 1.7 years (range, 1 week–9.9 years); 545 (42%) patients received pirfenidone for ≥2 years and 325 (25%) patients received pirfenidone for ≥4 years. The majority of patients (75.8%) received a mean daily dose of ≥1800 mg. Consistent with prior observations, gastrointestinal and skin-related events were among the most common treatment emergent adverse events (Table 1 ); these were almost always mild to moderate in severity, reversible with dose modification and rarely led to treatment discontinuation. Cough, dyspnoea and IPF were the most common respiratory adverse events in the integrated population—a finding that is consistent with expectations in patients with a chronic progressive respiratory disease followed over a long period of observation. Aminotransferase (ALT or AST) elevations (>3 × ULN) occurred in 40/1299 (3.0%) patients in the integrated population. Conclusions: A comprehensive integrated analysis of safety outcomes in a large, well–defined cohort of 1299 patients with IPF who were treated with pirfenidone for up to 9.9 years demonstrated that treatment with pirfenidone is safe and generally well tolerated. These observations provide further evidence to support the long-term clinical safety of pirfenidone in patients with IPF.